Development of a VSAT Based Virtual E- Learning System: (ARCSSTE-E as a Case study) - (:unkn) unknown (My University, 2017)
In this modern age, Information and communications technological innovations have turned the world into a small global village. E-Learning is one of the by-products of ICT and has been widely recognized as a valuable tool for learning and training other than the traditional method of learning (which involves physical contact between the student and the instructor). This paper presents the design of virtual classroom interface for teacher and student interaction using VSAT technology, which offers a tremendous potential to provide high-quality education to remote areas in Nigeria and Anglophone countries in Africa. Virtual classroom is a form of e-learning that acts as a supplement to the traditional learning methods, whereby, the physical contact is elusive and yet the classroom management is effective. The case-study for the proposed system is ARCSSTE-E. A conceptual framework for ARCSSTE-E is proposed and is developed to enhance and reach out to people within developing (Africa) countries that cannot make it to ARCSSTE-E due to constraint in time, distance, lack of sponsorship, Financial or other challenges. The study confirms the relevance of the growing interest in the use of virtual e-learning system for distance education.
Keywords: African Research